2014
DOI: 10.1007/s11033-013-2949-9
|View full text |Cite
|
Sign up to set email alerts
|

Major proteins in goat milk: an updated overview on genetic variability

Abstract: Milk and dairy products are very important in Mediterranean diet because of their health promoting and organoleptic properties. In many developing countries, goat rearing has a key role in livestock production. What makes goats so popular is their ability to provide high quality food under diverse climatic conditions and resilience to extreme and capricious environments. In the last years, the interest concerning caprine milk has been increasing also to find a new exploitation for local breeds. To promote the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 149 publications
0
71
0
5
Order By: Relevance
“…The casein genes are arranged in a 250 kb cluster on chromosome 6 in both cattle and goats (Ferretti et al, 1990;Threadgill & Womack, 1990), with the four genes organized in the order of alpha (α) s1 -casein, beta (β)-casein, alpha (α) s2 -casein, and kappa (κ)-casein (Caroli et al, 2006;Selvaggi et al, 2014). Among caseins, α s2 -casein accounts for approximately 20% of the total casein fraction in milk, compared with the 6% contribution of α s1 -casein (Selvaggi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The casein genes are arranged in a 250 kb cluster on chromosome 6 in both cattle and goats (Ferretti et al, 1990;Threadgill & Womack, 1990), with the four genes organized in the order of alpha (α) s1 -casein, beta (β)-casein, alpha (α) s2 -casein, and kappa (κ)-casein (Caroli et al, 2006;Selvaggi et al, 2014). Among caseins, α s2 -casein accounts for approximately 20% of the total casein fraction in milk, compared with the 6% contribution of α s1 -casein (Selvaggi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The demand for goat milk and goat milk products has increased rapidly in the last decade because of the belief that goat milk possesses unique biologically active, therapeutic and healthpromoting properties (Liang & Devendra, 2014). Goat milk is also more digestible than cow milk, which makes it more suitable for infants, small children, and adults that suffer from milk allergies and gastro-intestinal problems (Silanikove et al, 2010;Amigo & Fontecha, 2011;El-Agamy, 2011;Selvaggi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Milk and dairy products are important components of the Mediterranean diet (Selvaggi et al 2014), and it is proposed that they be consumed daily (Kastorini et al 2010). Additionally, dairy products (i.e., yogurt and cheese) have been shown more beneficially effective against atherogenesis and CVDs than milk (Tsorotioti et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is also an increasing need to consume goat milk, as a growing part of the population suffer from intolerance and allergy to other types of milk, such as cow milk (Selvaggi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The use of goat milk as a hypo-allergenic infant food or milk substitute in infants allergic to cow milk has been reported in much anecdotal literature [4,5]. In addition, some recent comparative human allergy and growth studies have been revealed that hypoallergenicity and growth rate of children were better in goat milk than those in cow milk [6,7].…”
Section: Introductionmentioning
confidence: 99%